Small launch platforms for micro-satellites - Cappelletti, Chantal; Battistini, Simone; Graziani, Filippo (Elsevier, 2018)
The number of small satellites launched into orbit has enormously increased in the last twenty years. The introduction of new standards of micro-satellites has multiplied the launch demand around the world. Nevertheless, not all the missions can easily have access to space: not all kinds of micro-satellites have granted a deployer system and, furthermore, once a micro-satellite is able to reach it, it cannot usually choose its final orbit. Recently two new platforms have been introduced for the release of micro-satellites as piggy-backs. These platforms are totally operative spacecrafts that act like motherships, and allow to select some parameters of the final orbit of the piggy-backs. They provide a solution for three different nano-satellites standard, and at the same time they are being developed in order to reach more powerful orbital release capabilities in the future. The design and the mission of these platforms are described in this paper.